2-mercaptothioxanthone as sensitizer and coinitiator for acylphosphine oxide photomitiators for: Free radical polymerization - Keskin, Sevnur; Jockusch, Steffen; Turro, Nicholas J.; Arsu, Nergis (AMER CHEMICAL SOC, 2008)
The initiation efficiencies of photoinitiators for free radical polymerization, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TMDPO) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphme oxide (BAPO), are enhanced by addition of mercaptothioxanthone (TX-SH) to the initiator formulation. The additive TX-SH combines the benefits of a triplet sensitizer (enhanced tight absorption) and-thiol functionality (reduced oxygen inhibition). On the basis of polymerization studies, laser flash photolysis, fluorescence, and phosporescence, the following mechanism is proposed: most of the light is absorbed by TX-SH to generate (3)(TX-SH)*, which transfers its energy to TMDPO and BAPO followed by alpha-cleavage to produce the initiating radicals. In addition, excellent polymerization yields were observed in air-saturated solutions when TX-SH was added. With the addition of TX-SH to initiation formulations, the inhibition due to oxygen is reduced, probably by the generation of reactive thiyl radicals by hydrogen abstraction of inactive peroxyl radicals from the thiol functionality.
Keywords: LASER FLASH-PHOTOLYSIS; ELECTRON-SPIN-RESONANCE; TIME-RESOLVED ESR; (2,4,6-TRIMETHYLBENZOYL)DIPHENYLPHOSPHINE OXIDE; RATE CONSTANTS; REACTIVITY; PHOTODECOMPOSITION; PHOTOINITIATORS; THIOXANTHONE; KINETICS; Polymer Science